1994
DOI: 10.1515/cclm.1994.32.4.293
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Chondroitin-6-Sulphate by a Competitive Enzyme Immunoassay Using a Biotinylated Antigen

Abstract: Summary: A competitive enzyme immunoassay was developed to determine chondroitin-6-sulphate in body fluids and cell cultures. The assay uses a monoclonal anti-chondroitin-6-sulphate antibody, immobilised to microtitre plates, and it involves a competitive binding reaction between chondroitih-6-sulphate in the samples and the biotinylated antigen.This assay enables the quantification of chondroitin-6-sulphate in the low concentration ränge of 16-120 g/l. The intra-assay and inter-assay coefficients of Variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Quantitation of chondroitin-6-sulfate Chondroitin-6-sulfate concentrations in cell lysates and cell culture medium were determined with a competitive enzyme immunoassay using biotinylated chondroitin-6-sulfate antigen as described before (Ka ¨hnert et al, 1994).…”
Section: Determination Of Xt Activitymentioning
confidence: 99%
“…Quantitation of chondroitin-6-sulfate Chondroitin-6-sulfate concentrations in cell lysates and cell culture medium were determined with a competitive enzyme immunoassay using biotinylated chondroitin-6-sulfate antigen as described before (Ka ¨hnert et al, 1994).…”
Section: Determination Of Xt Activitymentioning
confidence: 99%
“…In solid tumors such as colonic tumors, the stromata are rich in decorin (Adany et al, 1990) or CS (Wegrowski and Maquart, 2004). The overall CS‐concentration in human blood serum ranges between 5 and 30 µg/ml (Baici et al, 1992), and the concentration of CS‐6 sulfate (CS‐6S) was found to range between 55 and 169 ng/L in sera of healthy blood donors (Kähnert et al, 1994). The CS chains interact with a large number of ligands and receptors, which activate signaling pathways (Taylor and Gallo, 2006) and stimulate tumor growth.…”
mentioning
confidence: 99%
“…All chemicals used were of analytical grade or the highest grade commercially available. phate (9), hyaluronan) and markers specific for macrophages (neopterin, sCD14) (data not shown).…”
Section: Methodsmentioning
confidence: 89%